SUPPLY CHAIN MANAGEMENT DAN KINERJA ORGANISASI SME DI INDONESIA: PERAN MEDIASI DARI PRAKTEK HRM - Sari, Norma Rizky Kartika (Program Studi Manajemen Fakultas Ekonomi UST, 2024)
This study aims to explore the relationship between human resource management (HRM) practices, supply chain management (SCM) implementation, and small and medium enterprises (SMEs) performance in Indonesia. It also investigates whether HRM practices have a mediating effect on these relationships. Using a quantitative approach, the study involves 100 samples from various industries in a cross-sectional survey, collecting primary data through a multi-item questionnaire. The results of factor analysis and structural equation modeling indicate that SCM implementation and HRM practices positively contribute to SMEs' performance in Indonesia. Furthermore, it is found that HRM practices mediate the relationship between SCM implementation and SMEs' performance. This research provides original contributions by combining the simultaneous impact of SCM and HRM practices on SMEs' performance, explaining how internal management such as HRM practices influences SCM implementation in Indonesian SMEs. In conclusion, this study fills the literature gap regarding the influence of SCM on SMEs in Indonesia and offers a deeper understanding of these dynamics in the context of Indonesian business.